Pengaruh Konsentrasi Ekstrak Etanol Daun Mangga Arumanis Muda (Mangifera Indica L.) terhadap Hambatan Pertumbuhan Bakteri Streptococcus Mutans In Vitro - Kurniasih, Rizka; , drg. Mahmud Kholifa, MDSc (2016)
Dental caries is a dental hard tissue damage caused by plaque bacteria activity that has been fermenting arbohydrates. Streptococcus mutans is the dominant bacteria in dental plaque. Control of caries can be done in two ways: mechanically and chemically. Chemically conducted to inhibit the growth of bacteria that cause dental caries, one using the chlorhexidine mouthwash. But, the use of continuously will cause side effects such as discoloration of the teeth and mucosal irritation, and swelling of the parotid gland. Therefore, we need a mouthwash ingredients that can inhibit the growth of bacteria without side effects. One of the herbal ingredients that can be used as a mouthwash is arumanis young leaves of mango (Mangifera indica L.) because it has active substances such as mangiferin, flavonoids, alkaloids, triterpenoids and tannins. This study aims to examine the ability of various concentrations of ethanol extract of young leaves arumanis mango (Mangifera indica L.) against Streptococcus mutans bacteria growth inhibition and get a concentration of ethanol extract of young leaves arumanis mango (Mangifera indica L.) that has the ability equivalent to a positive control in inhibiting the growth of Streptococcus mutans bacteria. The method used in this research is the diffusion method. Subjects were divided into five groups being treated with ethanol extract of young leaves of mango arumanis concentration of 10%, 20%, 40%, 80% and 0.2% Chlorhexidine as a positive control. The results showed the ethanol extract of young leaves of mango arumanis 10% has the smallest inhibitory zone is 9.32 mm, the ethanol extract of young leaves of mango arumanis 80% have inhibitory zone who approached a positive control that is 13.83 mm and 0.2% Chlorhexidine has inhibitory zone of the total of 17.40 mm. One Way Anova Test results showed the P value = 0.00 (P <0.05) and the Post Hoc LSD test showed the P value = 0.00 (P <0.05). The conclusion the use of ethanol extract of young leaves arumanis mango (Mangifera indica L.) can significantly inhibit the bacteria Streptococcus mutans and there is a significant difference between the groups giving various concentrations of ethanol extract of young leaves arumanis mango (Mangifera indica L.) in inhibiting the growth of Streptococcus mutans.